THE PROPANORM EFFICACY IN RAPID RELIEF OF SYMPTOMS OF PAROXYSMAL AURICULAR FIBRILLATION - N. N. Borovkov; K. V. Mazalov; E. V. Sovetskaja; A. A. Vostokova; E. B. Malysheva; T. V. Koroleva; O. E. Vilkova (Российский кардиологический журнал, 2003)
In aim to study efficacy and safety of propafenone (Propanorm), open prospective поп randomized study in-patients with paroxysmal form of auricular fibrillation (AF) was carried out. 31 patients - 16 men (51,6 % ) and 15 women (48,4 % ) with mean age 58, 1± 8 years were included in the study. The paroxysmal form AF was observed in 29 patients (93,5 % ), persistent form - in 2 patients (6,5 % ). The reason of arrhythmia in 21 patients (67,7 % ) was ischemic heart disease, in 12 patients (38,7 % >) - arterial hypertension, in 2 patients (6,4 % ) - rheumatic heart diseases, in 1 patient (3,2 % ) - idiopathic AF. The medication for rapid relief of symptoms of paroxysmal auricular fibrillation was administered in single stress dose 600 mg per os. Propanorm restored the rhythm in 74,2 % > patients. The disorder of intraventricular conduction on EKG became evi-dentin 7 patients (22,5 % ) in time from 2to 16. 5 hours (on average 5, 1 hour), atrioventricular heart block of I stage - in 2 patients (6,45 % ), aberrant ventricular complex - in 2 patients (6,45 % ), pacemaker migration and sinus bradycardia - in 1 patient (3,2 % ). This disorders eliminated independently without special intervention. Extracardiac side effects during single intake were not observed. Propafenone appeared to be high-performed antiarrhythmic medication in rapid relief of symptoms of paroxysmal auricular fibrillation. Its application is possible in the outpatient setting.